Modelling of the high pressure-temperature effects on naringin hydrolysis based on response surface methodology - Marques, Joao (2015)
The aim of this study was the modelling, under high pressure, of naringin hydrolysis by naringinase. Response surface methodology (RSM) was used to compare the effects of the selected variables on the bioconversion under study. The combined action of temperature (13-61 degrees C) and pressure (80-216 MPa) on the catalytic activity of naringinase was investigated at pH 4.0 using naringin as the substrate. The choice of experimental domains resulted from preliminary studies. Naringinase activity, for naringin hydrolysis at pH 4.0, could be described by a convex surface with a maximum of 0.13 mM min(-1), at 41 degrees C and 158 MPa. After 1 h of reaction time, reducing sugars production could also be described by a convex surface, with a maximum reducing sugars concentration of 8 mM at 38 degrees C and 168 MPa. The interaction temperature-pressure had a significant effect on both naringinase activity and reducing sugar formation after 1 h. Under the optimized conditions, the naringin hydrolysis by naringinase was evaluated. (c) 2007 Elsevier Ltd. All rights reserved.